Aksumstelen. Et monuments skiftende betydninger - Whittaker, Helène (Nordlit, 2005)
This article deals with the various meanings associated with the Aksum stela which was taken from Ethiopia to Rome in 1937 and returned in 2005. It discusses its original meaning as a burial monument, its role in Mussolini’s propaganda, and the new meaning it has acquired after having been returned to Ethiopia and Aksum.
Keywords: propaganda; archaeological heritage; fascism; Mussolini; Augustus